2017
DOI: 10.18632/oncotarget.20927
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of long non-coding RNA Taurine Up-Regulated 1 inhibited doxorubicin resistance of bladder urothelial carcinoma via Wnt/β-catenin pathway

Abstract: In genitourinary system, bladder cancer (BC) is the most common and lethal malignant tumor, which most common type is bladder urothelial carcinoma (BUC). Long non-coding RNA (lncRNA) Taurine Up-Regulated 1 (TUG1) gene is high-expressed in several malignant tumors, including BC. In this study, over-expression of TUG1 was found in BUC tissues and cell line resistant to doxorubicin (Dox). Knockdown of TUG1 inhibited the Dox resistance and promoted the cytotoxicity induced by Dox in T24/Dox cells. TUG1 knockdown a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 35 publications
0
26
0
Order By: Relevance
“…Moreover, knockdown of these lncRNAs promoted UBC carcinogenesis and drug resistance. 5 7 , 24 , 25 Our results indicated that NEAT1 knockdown inhibited the sensitivity of J82 and T24 cells to DOX, which might provide a promising therapeutic target for UBC with DOX resistance.…”
Section: Discussionmentioning
confidence: 68%
“…Moreover, knockdown of these lncRNAs promoted UBC carcinogenesis and drug resistance. 5 7 , 24 , 25 Our results indicated that NEAT1 knockdown inhibited the sensitivity of J82 and T24 cells to DOX, which might provide a promising therapeutic target for UBC with DOX resistance.…”
Section: Discussionmentioning
confidence: 68%
“…Previous studies have suggested that lncRNA dysregulation in NSCLC is associated with lymph node metastasis, advanced stage, metastasis development, and poor patient prognosis. Anti‐tumor drug resistance in various carcinomas, including colon, bladder, ovarian, and gastric cancers, and NSCLC, is associated with lncRNAs. Although advances have been achieved in diagnosis and treatment, NSCLC is still one of the most common malignancies, with five‐year survival rates < 15% .…”
Section: Resultsmentioning
confidence: 99%
“…Numerous studies have suggested the importance of Wnt-b-catenin signaling in several cancers (44). Furthermore, Wnt-b-catenin has been shown to play important roles during epithelial-mesenchymal transition (45), cell proliferation and metastasis (24), and drag resistance (46) in bladder cancer. In the present study, RBM5 knockdown activated the Wnt-b-catenin pathway by promoting the expression of b-catenin and cyclin D1 while decreasing the apoptosis marker caspase-3 at the protein level.…”
Section: Discussionmentioning
confidence: 99%